Oversættelsesstrategier af retningsadverbiet ud i polske oversættelser af H.C. Andersens Eventyr & Historier - Smułczyński, Michał (Folia Scandinavica Posnaniensia, 2016)
The article is an investigation into strategies applied when translating Danish sentences with the directional adverb ud into Polish. The analyzed material consists of three different translations of a selection of H.C. Andersen’s fairytales into Polish, i.e. Cecylia Niewiadomska’s (1908), Stefania Beylin and Jarosław Iwaszkiewicz’s (1975) and Bogusława Sochanska’s (2006). The analysis is mainly focused on the Polish equivalents of Danish sentences with the directional adverb ud. However, since only Sochanska’s translation is a direct translation from Danish into Polish (the remaining ones are translations via German) the article’s analytical part also includes a comparison of strategies applied by the individual translators. Lastly, some comments are made with regards to the semantic status of the Danish directional adverb ud and its Polish equivalents.